Lipopolymers and lipids from lung surfactants in association with N-acetyl-l-cysteine: Characterization and cytotoxicity - Bujan, Ariana (2020)
In the present work, we obtained polymeric diacetylene liposomes that can associate N-Acetyl-L-Cysteine (NAC),a broad spectrum mucolytic. The reason for studying these formulations is that they could be applied in thefuture as NAC delivery systems, with a possible dose reduction but maintaining its effect.Liposomes used herein are obtained by a photopolymerization reaction, thus gaining stability and rigidity.Lipids belonging to lung surfactant were added in different ratios to the formulations in order to maximize itspossible interaction with the lung tissue. Because of lipopolymer stability, the oral or nasal route could beappropriated. This formulation could efficiently transport NAC to exert its mucolytic activity and help in diseasessuch as cystic fibrosis, which has abnormal mucus production. Also, this type of treatment could be useful inother types of diseases, interacting with the mucus layer and making the lung tissue more permeable to othertherapies.Formulations so obtained presented high levels of polymerization. Also, they present small hollow fibersstructures with a high number of polymeric units. These types of arrangements could present advantages in thefield of drug delivery, giving the possibility of a controlled release. Lipopolymers with lipids from lung surfactantassociated with NAC are promising complexes in order to treat not only respiratory illnesses. The stability of theformulation would allow its inoculation through other routes such as the oral one, helping the reposition of NACas an antioxidant drug. Finally, these formulations are non-toxic and easy to produce.